Controlling factors of Riedel shear spacing in the simple shear mode of strike-slip fault: Insights from sandbox models - Duan, Xu; Zhou, Weiwei; Han, Runsheng (Journal of structural geology, 2024)
Strike-slip faults generally develop Riedel shears (R-shears), which exhibit parallel and evenly-spaced distribution characteristics. However, the factors controlling the R-shear spacing in strike-slip faults are still unclear. The influence of material properties such as internal friction angle and cohesion, basal friction, and the thickness of brittle layers (T) on the R-shear spacing (S) are investigated using analogue models in this paper. Research findings indicate that the internal friction angle of the material and the thickness of the brittle layer have a significant impact on the R-shear spacing, with the thickness of the brittle layer directly determining the R-shear spacing as evidenced by their linear correlation. In comparison, cohesion and basal friction have insignificant effects on R-shear spacing. Based on this, experiments were carried out using various thicknesses of brittle layers (specified materials) to investigate the impact of the brittle layer thickness on the R-shear spacing, and Particle Image Velocimetry (PIV) is used to analyze the distribution pattern of R-shear development at each stage. The results indicate that fractures occur in regions where the vorticity field alternates between positive and negative values, and as the evolution progresses, the maximum strain gradually converges towards the center of the deformation zone, leading to a reduction in the activity of the R-shear, while the spacing of the R-shear remains unaltered. The normalized (S/T) results indicate that the experimental value of 1.32 aligns with natural laws and is very close to the normalized value of the natural faults, which is 1.24. It can be inferred that the thickness of the seismogenic crust within the range of the Altyn Tagh Fault is 40.9–43.5 km. •The sandbox experiment was used to explore the controlling factors of Riedel shear parallel and evenly-spaced in strike-slip faults.•Study the changes in Riedel shear spacing with different brittle layer thicknesses.•Apply the quantitative results of the experiment and the Riedel shear spacing derived from the Altyn Tagh fault to infer the thickness of the seismogenic crust.